THU0322 Does intense synovial enhancement in temporomandibular joints of juvenile idiopathic arthritis patients correlate with disease activity?. (23rd January 2014) - Zwir, L.; Terreri, M.T.; Sousa, S.; Fernandes, A.; Guimarães, A.S.; Hilário, M.O.
Abstract : Background: The temporomandibular joint (TMJ), like any other synovial joint, may be involved in Juvenile Idiopathic Arthritis (JIA). According to the literature, the frequency of TMJ involvement varies from 17-87%, depending on the population under study, on the subtypes of the disease and on the method used to evaluate joint involvement. Condylar damage may be present early in the disease course and progress even in absence of clinically detectable symptoms or signs. Gadolinium-enhanced magnetic resonance imaging (MRI) is considered to be the gold standard in diagnosing early inflammatory changes of the TMJ in patients with JIA. Objectives: The aims of our longitudinal study were to perform a comprehensive clinical evaluation of temporomandibular joint (TMJ) and to investigate the association between the magnetic resonance imaging (MRI) and clinical findings in TMJs and the disease activity of patients with JIA. Methods: Seventy five patients with JIA participated in this study and were divided into 3 groups: patients with active disease, patients with clinical remission on medication and patients with clinical remission off medication. Thirty-nine patients had oligoarticular course and 36 had poliarticular/ systemic course. All patients underwent a rheumatologic examination performed by a pediatric rheumatologist, a TMJ examination performed by a dentist and MRI of the TMJs. These examinations were scheduled at the same date. The patients were examined again with one-year interval. Results: The mean age at diagnosis was 6.0 years and the mean age at the first examination was 12.4 years. According to the degree of activity at the first examination, 33 patients were characterized as active, 21 were in remission on medication and 21 were in remission off medication. At the second examination, 21 patients were active, 28 were in remission on medication and 26 in remission off medication. At the first examination no symptoms were reported in 47 (62.7%) of patients and at the second evaluation in 64 (85.3%). The most common symptoms were pain in function, TMJ sounds and pain at rest. Synovial enhancement was present in 70 (93.3%) patients at the first phase exams compared with 65 (86.7%) at the second phase, one year apart. Intense contrast enhancement was significantly associated with active disease only at the first evaluation (p=0.0008), with poly/systemic subtypes at both evaluations (p=0.028 and p=0.049 respectively), with the presence of erosions at both evaluations (p=0.0001 and p<0.0001 respectively) and with altered condylar shape at the second evaluation (p=0.0005). Conclusions: The TMJ should always be evaluated in JIA patients even in the absence of signs and symptoms; accordingly to the current established concepts TMJ synovial enhancement could be present even in patients in remission; although synovial enhancement is considered the gold standard in assessing TMJ involvement, we should be cautious in interpreting this finding. Disclosure of Interest: None Declared